2004
DOI: 10.1158/0008-5472.can-04-0424
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for Carcinoembryonic Antigen-Related Cell Adhesion Molecule 6 as a Determinant of Gemcitabine Chemoresistance in Pancreatic Adenocarcinoma Cells

Abstract: Most patients with pancreatic adenocarcinoma present with surgically incurable disease. Gemcitabine, the principal agent used to treat such patients, has little impact on outcome. Overexpression of carcinoembryonic antigen-related cell adhesion molecule (CEACAM) 6, a feature of this malignancy, is associated with resistance to anoikis and increased metastasis. The purpose of this study was to determine the role of CEACAM6 in cellular chemoresistance to gemcitabine. CEACAM6 was stably overexpressed in Capan2 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 30 publications
7
73
0
2
Order By: Relevance
“…One possible explanation of the relationship between overexpression of CEACAM6 and gemcitabine resistance is that CEACAM6 overexpression may protect cells from cytochrome c-induced caspase 3 activation and apoptosis via Akt or c-Src activation. This cytoprotective pathway may contribute to gemcitabine chemoresistance (Duxbury et al, 2004e). …”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation of the relationship between overexpression of CEACAM6 and gemcitabine resistance is that CEACAM6 overexpression may protect cells from cytochrome c-induced caspase 3 activation and apoptosis via Akt or c-Src activation. This cytoprotective pathway may contribute to gemcitabine chemoresistance (Duxbury et al, 2004e). …”
Section: Discussionmentioning
confidence: 99%
“…Really, activation of Src has been reported in various cancers characterized by anoikis resistance [48,69,114,115]. Actually, a crucial role is played by the modulation of PI3K-Akt signal pathway, regulated by PTEN-mediated dephosphorylation [116].…”
Section: Taddei Et Almentioning
confidence: 99%
“…To this end, we screened a panel of pancreatic cancer cell lines for sensitivity to adenovirus and then examined differential gene expression between adenovirus-sensitive and -insensitive cells by Affymetrix array analysis. Interestingly, we found that expression of carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6), a gene with a well-documented role in tumor invasion, metastasis, and drug resistance (17)(18)(19)(20), correlates with the sensitivity of tumor cells to adenovirus. Further stepwise investigations demonstrated that CEACAM6 blocked adenovirus trafficking to the nucleus through the Src pathway, which interferes with the cytoskeleton of cancer cells, resulting in attenuated infectability by adenovirus.…”
Section: Introductionmentioning
confidence: 99%